Reconstructing Students’ Critical Thinking Skills in Science and Social Studies through the STAD Cooperative Learning Model in Elementary Schools - Azzah Tsabitah Ruwaidah; Anggit Grahito Wicaksono; Mukhlis Mustofa (Program Studi PGSD Universitas Madako Tolitoli, 2026)
Departing from the not optimal critical thinking skills of grade V students in social studies learning at SDN Gugus IV Hasanuddin Surakarta, this study aims to evaluate the effectiveness of the implementation of the Student Teams-Achievement Divisions (STAD) type cooperative model. The study used a quantitative approach with a quasi-experimental posttest-only nonequivalent control group design, involving 53 students divided into experimental and control classes. Data was obtained through a critical thinking ability test equipped with observation and documentation, then analyzed using the Independent Samples t-Test after meeting the assumptions of normality and homogeneity. The results of the analysis showed that the average score of the experimental group reached 74.62, higher than the control group of 52.04, with a significance value of 0.000 (p<0.05). These findings confirm that the implementation of STAD makes a real contribution to improving the quality of students' critical reasoning. Such effectiveness is related to the intensity of group interaction and the active involvement of students in solving problems. Thus, the STAD model has important implications as a relevant learning strategy to strengthen critical thinking skills in the context of science and science learning in elementary schools.